RESERVOIR STRUCTURE ANALYSIS PLANNING NEEDS WATER SUPPLY IN VILLAGES RIVER NORTH SAMARINDA DISTRICT SAMARINDA CITY - RAMLY, AHMAT (KURVA S JURNAL MAHASISWA, 2016)
IN THIS THESIS RESEARCH DISCUSSES THE CALCULATION AND ANALYSIS OF RESERVOIR BUILDING STRUCTURE NEED CLEAN WATER. IT IS INTENDED TO ANALYSZE THE LOADS THAT WORK ON BUILDING RESERVOIR AND ANALYSIS NEEDS CLEANS WATER WHERE THE STUDY WAS CONDUCTED. THE PLANNED RESERVOIR Â THATS IS SEMI GROUND, THERE IS A STRUCTURE THAT IS EMBEDDED IN GROUND.